Volatility Spillover between Indonesian Stock Market and Gold during Covid-19 Pandemic - Christopher Anthony Surya Dharma; Robiyanto Robiyanto; Harijono Harijono; Triyanto Triyanto (Universitas Sahid, 2024)
This study scrutinizes the influence of Covid-19 toward returns and volatility spillover on the Indonesian stock market and international gold price. This study employs secondary data from investing.com. Data used in this study are closing price and returns of the Indonesian stock market and international gold price. Data were analyzed by using BEKK-GARCH techniques. The results obtained from this study show there is strong relationship between volatility spillover and return exists. JCI returns and gold returns are affected by the spillover volatility both before Covid-19, during Covid-19 and overall period. The return value tends to be inversely proportional to volatility, where when volatility overflows, the return will decrease and vice versa. Monitoring the volatility spillover between the stock market and gold prices can help in risk management and being able to see the relationship between the stock market and gold prices can help identify the level of correlation between two instruments.